(untitled) - Eitan M Gurari (New York, 1994)
The book provides a short introduction to the most basic features of TeX and LaTeX. It also introduces enhancements for drawing and for programming with TeX and LateX
Keywords: computerrized typesetting,mathematics printing - computer programms,tex ( computer file )